LEGAL PROTECTION OF ECONOMIC RIGHTS OF BUSINESS ACTORS AGAINST COUNTERFEITING AND CIRCULATION OF COUNTERFEIT COSMETIC BRANDS - Liandhajani Liandhajani; Tuti Widyaningrum (Yayasan Education and Social Center, 2022)
This study aims to analyze Law Number 20 of 2016 concerning Brands and Geographical Indications, and the role of government in related agencies is not optimal in protecting business actors from counterfeiting cosmetic product brands. The method used is normative juridical. The research result is that as a consideration of the changes to Indonesian Law Number 15 of 2001 concerning Marks to Indonesian Law Number 20 of 2016 concerning Marks and Geographical Indications that in the era of global trade, in line with international conventions that have been ratified by Indonesia, licensing of trademarks and Geographical Indications are very important, especially in maintaining fair and just business competition, protecting consumers, and also protecting Micro, Small and Medium Enterprises and domestic industries, it is also to improve services further and provide legal certainty for the world of industry, trade and investment in facing the development of local, national, regional and international economy also the development of information and communication technology, it is necessary to be supported by an adequate statutory regulation in the field of Marks and Geographical Indications. Based on the positive law in Law No. 20 of 2016 concerning Brands and Geographical Indications. That the mark is an Intellectual Property Right protected by the government and the law. So, the writer can conclude that those who violate or plagiarize a well-known mark can be subject to imprisonment and a fine as described in the law because the mark is a protected asset. The government has also made an appeal or socialization regarding the importance of Intellectual Property Rights (IPR), and trademarks are included in (IPR).